ChemInform Abstract: A Convenient Tandem One‐Pot Synthesis of Donor—Acceptor‐Type Triphenylene 2, 3‐Dicarboxylic Esters from Diarylacetylene. Issue 8 (February 2015) - Feng, Chun; Tian, Xian‐Li; Zhou, Jing; Xiang, Shi‐Kai; Yu, Wen‐Hao; Wang, Bi‐Qin; Hu, Ping; Redshaw, Carl; Zhao, Ke‐Qing
Abstract A new strategy for the direct synthesis of donor‐acceptor‐type triphenylene 2, 3‐dicarboxylic esters in a one‐pot manner through a cascade reaction involving enyne metathesis of diarylacetylene, cycloaddition with a dienophile, and subsequent aromatization and oxidative cyclodehydrogenation is developed.